2021
DOI: 10.1007/s11240-021-02140-0
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and experimental field cultivation of Pulsatilla turczaninovii Kryl. et Serg. (Ranunculaceae)

Abstract: Pulsatilla turczaninovii is an important medicinal plant, valued for high ornamental value of melliferous flowers. We assessed the efficiency of reproduction under in vitro conditions and the ex situ growth capacity of this important representative of the world flora. The seed germination percentage was assessed, followed by determination of micropropagation rate and rooting efficiency. Then, the possibility of plant development in three consecutive growing seasons was assessed. The in vitro germination percen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Several Pulsatilla species, e.g. P. grandis , P. koreana 47 , P. patens 12 , 47 , P. pratensis 48 – 50 , P. turczaninovii 51 , P. vernalis and P. vulgaris 33 , were multiplied by in vitro organogenesis and/or somatic embryogenesis, acclimatized to ex vitro and to semi-natural conditions. However, in none of these experiments, regenerated plants were re-introduced to the natural (extinct) populations, and their genetic uniformity was not confirmed with the initial material.…”
Section: Discussionmentioning
confidence: 99%
“…Several Pulsatilla species, e.g. P. grandis , P. koreana 47 , P. patens 12 , 47 , P. pratensis 48 – 50 , P. turczaninovii 51 , P. vernalis and P. vulgaris 33 , were multiplied by in vitro organogenesis and/or somatic embryogenesis, acclimatized to ex vitro and to semi-natural conditions. However, in none of these experiments, regenerated plants were re-introduced to the natural (extinct) populations, and their genetic uniformity was not confirmed with the initial material.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that using seeds for plant propagation may increase genetic variability and maximize the repopulation of sexually originated plants such as Pulsatilla turczaninovii , Viola cornuta , Echinacea angustifolia and others [ 17 , 18 , 19 , 20 , 21 ]. However, there is some dispute about whether Agave species produce viable seeds for propagation [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%